Pengaruh Audit Internal Dalam Kasus Penyalahgunaan Laporan Keuangan Pada PT Tiga Pilar Sejahtera - Fiqri Najmuddien; Nurfadilah Nurfadilah; Irda Agustin Kustiwi (BADAN PENERBIT STIEPARI PRESS, 2024)
This study aims to analyze the effect of internal audit on the prevention and detection of misuse of financial statements. The variable object of this study is PT Tiga Pilar Sejahtera. Misuse of financial statements can harm stakeholders and damage the integrity of the company. Therefore, the role of internal audit is considered important in ensuring the reliability and validity of financial information presented by the company. This research contributes to an understanding of the important role of internal audit in securing the integrity of a company's financial statements and provides recommendations for similar companies to strengthen their internal control systems. The practical implication of this study is the importance of companies to pay special attention to the internal audit function to reduce the risk of misuse of financial statements that can harm the company and its stakeholders. This article is a quantitative descriptive using secondary data.